Fronto-Temporal Connectivity Predicts ECT Outcome in Major Depression - Leaver, Amber M.; Wade, Benjamin; Vasavada, Megha; Hellemann, Gerhard; Joshi, Shantanu H.; Espinoza, Randall; Narr, Katherine L. (Frontiers in Psychiatry, 2018)
Background: Electroconvulsive therapy (ECT) is arguably the most effective available treatment for severe depression. Recent studies have used MRI data to predict clinical outcome to ECT and other antidepressant therapies. One challenge facing such studies is selecting from among the many available metrics, which characterize complementary and sometimes non-overlapping aspects of brain function and connectomics. Here, we assessed the ability of aggregated, functional MRI metrics of basal brain activity and connectivity to predict antidepressant response to ECT using machine learning. Methods: A radial support vector machine was trained using arterial spin labeling (ASL) and blood-oxygen-level dependent (BOLD) fMRI metrics from n=46 (26 female, mean age 42) depressed patients prior to ECT (majority right-unilateral stimulation). Image preprocessing was applied using standard procedures, and metrics included cerebral blood flow (CBF) in ASL, and regional homogeneity (ReHo), fractional amplitude of low-frequency modulations (fALFF), and graph theory metrics (strength, local efficiency and clustering) in BOLD data. A 5-repeated 5-fold cross-validation procedure with nested feature selection validated model performance. Linear regressions were applied post hoc to aid interpretation of discriminative features. Results: The range of balanced accuracy in models performing statistically above chance was 58-68%. Here, prediction of nonresponders was slightly higher than for responders (maximum performance 74% and 64%, respectively). Several features were consistently selected across cross-validation folds, mostly within frontal and temporal regions. Among these were connectivity strength amongst: a fronto-parietal network (including left dorsolateral prefrontal cortex), motor and temporal networks (near ECT electrodes), and/or subgenual anterior cingulate cortex. Conclusions: Our data indicate that pattern classification of multimodal fMRI metrics can successfully predict ECT outcome, particularly for individuals who will not respond to treatment. Notably, connectivity with networks highly relevant to ECT and depression were consistently selected as important predictive features. These included the left dorsolateral prefrontal and the subgenual anterior cingulate cortex, which are both targets of other neurostimulation therapies for depression, as well as connectivity between motor and right temporal cortices near electrode sites. Future studies that probe additional functional and structural MRI metrics and other patient characteristics may further improve the predictive power of these and similar models.